Understanding Laughter in Dialog - Koutsombogera, Maria; Vogel, Carl (My University, 2022)
This work explores laughter within a corpus of three-party, task-based dialogs with native and non-native speakers of English, each consisting of two players and a facilitator, in relation to whether the laughter is perceived as serving discourse functions or rather as genuinely mirthful according to a small number of annotators’ (2) inspection of a substantical multimodal dialog corpus (18 interactions of approximately 10 min each). We test the hypothesis that those different types of laughter have occurrence patterns that relate in different ways to the topical structure of the conversations, with discourse laughter showing a stronger tendency to occur at topic termination points. All laughter events (569) are assigned to one of three values, discourse, mirthful or ambiguous, and are studied with respect to their distribution across the dialog topic sections. The analysis explores interactions among laughter type and section type, also with respect to other variables such as the facilitators’ feedback and the speakers’ conversational role and gender. Discourse laughter is more frequent at topic termination points than at topic beginnings, also in comparison to mirthful laughter. Discourse laughter is also highly associated with facilitators’ feedback type, especially at topic ends. Finally, there are few distinctive effects of gender, and an interaction among speaker role and laughter type. The results strengthen the hypothesis of the discourse function of laughter, indicating a systematicity in discourse laughter, in that it is more predictable and highly associated with the dialog topic termination points, and, on the contrary, a less systematic distribution of mirthful laughter, which shows no particular pattern in relation to topic boundaries.
PUBLISHED
Keywords: Conversational laughter; Topic boundaries; Laughter rate; Discourse laughter; Discourse marker; Dialog; Cognitive Development/Processes